2015
DOI: 10.3201/eid2107.150226
|View full text |Cite
|
Sign up to set email alerts
|

Gastroenteritis Outbreaks Caused by Norovirus GII.17, Guangdong Province, China, 2014–2015

Abstract: In the past decade, the most prevalent norovirus genotype causing viral gastroenteritis outbreaks worldwide, including China, has been GII.4. In winter 2014–15, norovirus outbreaks in Guangdong, China, increased. Sequence analysis indicated that 82% of the outbreaks were caused by a norovirus GII.17 variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
133
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(141 citation statements)
references
References 11 publications
6
133
2
Order By: Relevance
“…Surveillance in China has shown that norovirus GII.17 predominated over GII.4 Sydney as the cause of outbreaks during the 2014–15 season ( 9 ). The sequences reported in that study showed a high similarity with the Hu/GII.17/Gaithersburg/2014/US strain and clustered within GII.17 cluster C. Thus, we conclude that the same GII.17 virus that caused outbreaks in Asia was present in the United States near the beginning of the 2014–15 season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveillance in China has shown that norovirus GII.17 predominated over GII.4 Sydney as the cause of outbreaks during the 2014–15 season ( 9 ). The sequences reported in that study showed a high similarity with the Hu/GII.17/Gaithersburg/2014/US strain and clustered within GII.17 cluster C. Thus, we conclude that the same GII.17 virus that caused outbreaks in Asia was present in the United States near the beginning of the 2014–15 season.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that GII.4 strains successfully persist and infect humans by the periodic emergence of new GII.4 variants that escape from herd immunity developed against previous variants ( 8 ). Recently, increased detection of GII.17 as the predominant outbreak strain in China has been reported ( 9 ). In this study, we characterized the genome of a norovirus GII.17 strain recently detected in Maryland, USA, to determine whether the same GII.17 virus is spreading globally.…”
mentioning
confidence: 99%
“…It attacked Beijing, Guang--dong, Hebei, Jiangsu, Zhejiang, Taiwan and Hongkong [20][21][22][23][24][25][26][27][28][29][30][31][32] . Besides, other rare prevalent genotypes were also confirmed, including GII.6 [33,34] and GIV.1 [35] .…”
Section: Gii4 Syndey As the Course Of Outbreaks Inmentioning
confidence: 99%
“…China [15,[20][21][22][23][24][25][26][27][28][29][30][31][32] . It attacked Beijing, Guang--dong, Hebei, Jiangsu, Zhejiang, Taiwan and Hongkong [20][21][22][23][24][25][26][27][28][29][30][31][32] .…”
Section: Gii4 Syndey As the Course Of Outbreaks Inmentioning
confidence: 99%
“…For example, over the last 2 decades, new genogroup II genotype 4 (GII.4) variants have emerged every 2 to 4 years (4,5). In the winter of 2014 to 2015, a novel norovirus GII.17 Kawasaki 2014 variant replaced the predominant GII.4 Sydney 2012 variant in several Asian countries (6)(7)(8)(9). Here, we report on the reduced diagnostic performance of two commonly used commercial norovirus EIAs for this emergent GII.17 variant.…”
mentioning
confidence: 99%